For the love of Europe : my favorite places, people and stories - Steves, Rick, 1955- (Avalon Travel, Hachette Book Group, 2020)
Join Rick as he's swept away by a fado singer in Lisbon, learns the dangers of falling in love with a gondolier in Venice, and savors a cheese course in the Loire Valley. Contemplate the mysteries of centuries-old stone circles in England, dangle from a cliff in the Swiss Alps, and hear a French farmer's defense of foie gras. With a brand-new, original introduction from Rick reflecting on his decades of travel, For the Love of Europe features 100 of the best stories published throughout his career. Covering his adventures through England, France, Germany, Ireland, Italy, the Netherlands, Spain, and more, these are stories only Rick Steves could tell.